Methodologies and methods of transnational learning - Mariussen, Åge; Virkkala, Seija (Routledge, 2013)
Introduction Most of the time, cognitive learning (see Chapter 1, this volume) is likely to be enabled and restricted by spatial (see Chapter 2, this volume) and organizational (see Chapter 3, this volume) frameworks, and lock-in mechanisms, which create trajectories. Attempts at transnational learning are often motivated by visions that break with some of these spatial and organizational limitations, sometimes with reference to emergent (Chapter 1) institutional phenomena or megatrends driven by globalization. The examples used in this volume are liberalization (NPM), multilevel governance in Europe (OMC, Smart Specialization), global communities defending the common interests of humanity (World Heritage), and Nordic values (see Chapters 1, 6, 8 and 13, this volume). The special case of Nordic learning is discussed more comprehensively in Chapter 8. This chapter shows how some of these forms of transnational learning may be analyzed within the parameters defined by SECI (see Chapter 3, this volume). The argument is that new knowledge creation facilitated through the analytical and organizational tools of SECI has a potential to change trajectories usually locked in by spatial and organizational restrictions. Accordingly, in the discussion on methods (see below), the chapter refers to approaches and tools that are based on SECI, which may be useful in organizing, monitoring and evaluating processes of transnational learning. In doing so, we draw upon some of the concepts introduced by Mariussen and Virkkala in Chapter 4 of this volume, such as translation and abduction. Finally, in the discussion on the practical application of the outcomes of transnational learning and innovation, the topic of emergence, introduced in Chapter 1, is reopened, from the point of departure of theories of institutional change. It is argued that continued work in this direction enables the development of analytical and methodological tools which may be used to explore empirically how transnational learning can change trajectories (see below).
Keywords: learning; change; cooperation (general); organisations (systems); welfare state; modeling agencies; learning organisation; welfare state; enterprises; regional development; fi=Aluetiede|en=Regional Studies|